Stability of the Functional Equation Deriving From Quadratic Function in Banach Space - Amrit; Kumar, Anil; Antil, Manoj Kumar (Communications in Mathematics and Applications, 2024)
In this manuscript, we introduce a quadratic functional equation of finite variable: align onumber _i=1^m φ (2v_i-_1 ≤ i eq j^m v_j)&=(m-7)_1 ≤ i <j ≤ m φ (v_i+v_j)+φ(_i=1^m v_i) onumber &-(m^2-9m+5) _i=1^m φ(v_i) align and examine its Hyers-Ulam stability of this functional equation in Banach space using direct and fixed point method.